Minimally invasive techniques in thymic surgery (review of literature) - O. V. Pikin; A. B. Ryabov; D. Ye. Martinova; Z. M. Salimov (Вестник хирургии имени И.И. Грекова)
We carried out the systematic review of the domestic and foreign literature focusing on surgical treatment of patients with thymic pathology. Special attention was paid to the discussion of the advantages of minimally invasive surgery, particularly, video endoscopic thymectomy from subxiphoid access. Pubmed, Medline and E-library databases were searched for retrospective and prospective randomized trials. Based on the analysis of literature sources, we presented the data on tumor and non-tumor pathology of the thymus gland, clarified indications for surgical treatment in different types of thymic pathology. Variants of thymectomy were described, a brief historical review of the use of the surgical method in patients with thymus gland pathology was conducted. The technique of surgeries, advantages and weak points of various surgical approaches were described. We focused our attention on minimally invasive interventions, listed its advantages in comparison with the standard “open” surgical approach. The contemporary trends in surgical approaches in thymus pathology were discussed. Minimally invasive thymectomy is modern, safe and feasible variant of surgical treatment of patients with tumor and non-tumor pathology of the thymus gland. The subxiphoid approach allows to reduce postoperative pain, provides an excellent view of mediastinal structures and both pleural cavities, which improves the safety of operation with satisfactory cosmetic results.